1994
DOI: 10.1093/ajcp/102.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Flow-cytochemical Differential Leukocyte Analysis with Quantitation of Neutrophil Left Shift:An Evaluation of the Cobas-Helios Analyzer

Abstract: The Cobas-Helios (Roche Diagnostic Systems, Inc., Branchburg, NJ) is a new, fully automated hematology analyzer that performs a complete blood count and differential leukocyte count (DLC), classifying leukocytes by flow-cytochemical technology. The DLC component of the Cobas-Helios was evaluated according to the National Committee for Clinical Laboratory Standards H20-A protocol. Instrument performance was acceptable with respect to all parameters investigated, including imprecision, inaccuracy and clinical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
2
5
0
1
Order By: Relevance
“…Based on the coefficient of variation as a measure of basophil reproducibility, hematology analyzers usually appeared exceptionally imprecise (1,3,5,7), which is consistent with our findings. However, we found the number of theoretically differentiated leukocytes to be in the same range as for other leukocyte classes (12), which indicated that to a great extent this high imprecision is due to the smallness of the basophil population rather than only to differentiation-related problems.…”
Section: Discussion Precisionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the coefficient of variation as a measure of basophil reproducibility, hematology analyzers usually appeared exceptionally imprecise (1,3,5,7), which is consistent with our findings. However, we found the number of theoretically differentiated leukocytes to be in the same range as for other leukocyte classes (12), which indicated that to a great extent this high imprecision is due to the smallness of the basophil population rather than only to differentiation-related problems.…”
Section: Discussion Precisionsupporting
confidence: 91%
“…Basophil count results frequently showed a high imprecision and poor results in regression analysis against the manual differential, the presently accepted reference method (1)(2)(3)(4)(5). Some investigators conceded that, due to the inadequacies of this reference method (5)(6)(7) and the shortcomings of least-squares linear regression (3), the validity of these results was doubtful.This situation, however, is far from satisfying considering the time and money manufacturers have spent on implementing basophil counting on their hematology analyzers.…”
Section: Introductionmentioning
confidence: 99%
“…1), our correlation results of the STKS were better than in most other studies (3,8,9,22,23). The mean negative bias against the manual dif- •Inc., Branchburg, NJ, USA), which is very similar to the Argos, and found a positive mean bias (24), probably due to a different setting of discriminators in the Argos scattergramme. Such an.…”
Section: Precisionmentioning
confidence: 67%
“…[9][10][11] Despite the effort put into the development of analyzer flagging, its efficiency in the present study was not substantially superior to that of the absolute neutrophil count.…”
Section: Detection Of Left Shiftmentioning
confidence: 85%